2002
DOI: 10.1046/j.1524-4725.2002.02041.x
|View full text |Cite
|
Sign up to set email alerts
|

Does the Recipient Site Influence the Hair Growth Characteristics in Hair Transplantation?

Abstract: These results strongly suggest that the recipient site affects some characteristics of transplanted hairs, such as their growth and survival rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…According to Hwang et al hair follicles transplanted from the occipital scalp to lower leg took on the hair characteristics of leg hair and partially the same hair reversed their characteristics when transplanted to the nape of the neck. [32] This is supported by Woods and Campbell, who using chest hair micro grafts transplanted to the scalp showed extended growth and almost 4 times increase in their length to mimic growth characteristics of the native scalp hairs in the crown region. [33]…”
Section: Discussionmentioning
confidence: 80%
“…According to Hwang et al hair follicles transplanted from the occipital scalp to lower leg took on the hair characteristics of leg hair and partially the same hair reversed their characteristics when transplanted to the nape of the neck. [32] This is supported by Woods and Campbell, who using chest hair micro grafts transplanted to the scalp showed extended growth and almost 4 times increase in their length to mimic growth characteristics of the native scalp hairs in the crown region. [33]…”
Section: Discussionmentioning
confidence: 80%
“…In another study of ours, hair transplantation from the occipital scalp to various recipient sites such as the lower leg, nape of the neck, palm, and lower back was performed, and it showed the decrease of the anagen period and the rate of growth when scalp hairs were transplanted to the body site. 2 Consequently, these observations suggested that the recipient site affects some characteristics of transplanted hairs, such as their growth rate and anagen phase. One uncertainty was whether body hair characteristics, such as growth rate and the anagen period, would be affected if the concept of recipient site influence was valid.…”
Section: Discussionmentioning
confidence: 99%
“…We suggested that the recipient site influences the growth characteristics of transplanted hairs such as growth rate and anagen period when transplanted scalp hairs were transplanted to different recipient sites such as the lower leg, neck, palm, hand dorsum, and eyebrow. 2,3 The purpose of this study was to evaluate whether the body hairs would keep their original growth characteristics when the body hairs were transplanted to the scalp area.…”
mentioning
confidence: 99%
“…In this study, the mean survival rate of single-hair grafts of 73.6 7 7.6% correlated with patient's age. Hwang and associates 22 suggested that the recipient site affects some characteristics of transplanted hairs, such as their growth and survival rate. The survival rate on the lower leg was 60.2%.…”
Section: Discussionmentioning
confidence: 99%